Technical characteristics and economic performance of commercial tilapia hatcheries applying different management systems in Egypt - Nasr-Allah, A.M.; Dickson, M.W.; Al-Kenawy, D.A.R.; Ahmed, M.F.M.; El-Naggar, G.O. (Elsevier, 2014)
This study was carried out in order to understand the technical and economic characteristics of different Egyptian Nile tilapia (Oreochromis niloticus) hatchery systems. Hatchery operators at fifty tilapia hatcheries in four governorates were interviewed and four focus group discussions were held with 61 participants in March 2012. Technical characteristics and economic performance data were obtained for three tilapia hatchery systems: hapa-based in earthen ponds (hapa), hapa-based in greenhouse tunnels (greenhouse) and concrete tanks in greenhouse tunnels with water heating (heated greenhouse).